Determinants of Brand Loyalty in the Skincare Industry: The Influence of Brand Satisfaction and Brand Trust among MS Glow Consumers - Julaiha; Humaidi; Hairudinor; Setio Utomo (Journal of Business Transformation and Strategy, 2026)
Abstract: This study aims to test the partial and simultaneous influence of brand satisfaction and brand trust on brand loyalty on MS Glow products in Banjarmasin City. The method used is a quantitative approach. The sample in this study amounted to 96 respondents who were MS Glow users obtained through purposive sampling techniques. Data collection was carried out using a questionnaire and analyzed using multiple linear regression. The results of the study indicate that brand satisfaction has a positive and significant effect partially on brand loyalty. Meanwhile, brand trust has a positive but not significant effect partially on brand loyalty. Simultaneously, brand satisfaction and brand trust have a positive and significant effect on brand loyalty on MS Glow products in Banjarmasin City